TRANSFORMASI DIGITAL: EVOLUSI KOMUNIKASI MASSA DI ERA MEDIA SOSIAL DAN DAMPAKNYA PADA PERILAKU KONSUMSI INFORMASI MASYARAKAT - Rosa Amalia Bamasputri; Icha Fitriani; Asri Agustina Salsabila; Nur Indah Dwi Prasetyaningsih (STKIP Subang, 2025)
The digital age has brought significant transformations in the way we communicate, especially with the presence of social media which is now the main channel for disseminating news and information. This study seeks to examine how mass communication develops in the era of social media, as well as its impact on people's behavior in receiving information. The approach used is a Systematic Literature Study (SLS) combined with a literature review of various scientific sources, research articles, and other relevant references published in the last ten years. The study results reveal that social media has drastically changed the flow of information. People are now not only recipients, but also active creators of information content. This has triggered a change in information consumption habits to become faster, more concise and fragmented. This research highlights the importance of digital literacy in dealing with the dynamics of mass communication today, and advocates for increased critical education regarding the use of social media.